Oral Pathology in Digestive Diseases - Elena POPESCU; Ana Maria Alexandra STANESCU (Modern Medicine)
Correlations between alterations in the oral cavity and systemic conditions have been widely reported. A considerable number of gastrointestinal (GI) diseases of varied nature may produce lesions in the hard and soft oral tissues. Among the different types of manifestations of GI, oral lesions represent an important, if not a major component of the manifestation of these diseases. As a consequence, recognition and management of oral lesions accompanying the GI conditions, is mandatory for all clinicians, either gastroenterologists or dentists. The aim of this article is to underline useful data about the most common GI conditions (intestinal bowel diseases (IBD), gastroesophageal reflux, genetic diseases, malabsorption conditions, infections, metastatic tumors) and their link to oral pathology.